A visit to Malaysian Palm Oil Board (MPOB) headquarters, Bandar Baru Bangi - Choong, Thomas Shean Yaw, Ir. Prof. Dr. (The Institution of Engineers, Malaysia, 2013)
Link to publisher’s homepage at http://www.myiem.org